Formal and informal learning transfer in the workplace - Royce Ann Collins; Connie Carpenter (Adult Education Research Conference, 2020)
Both employees and organizations invest significant amounts of time, energy, and funds while promoting knowledge development as a fulcrum for increasing reflexive transformation, gaining higher cognitive skills, and achieving both organizational and workforce members’ performance goals. Our paper advocates multi-faceted and interactionist adult learning approaches designed to stimulate learners’ motivational dispositions as they transition to and from formal and informal learning environments.
Keywords: Formal learning; informal learning; reflexive transformation; motivational disposition